The Malay World: Connecting the Past to the Present - Habana, Olivia Anne (Archīum Ateneo, 2017)
In the late 19th century – early 20th century, colonial regimes in Southeast Asia introduced programs for the education and formation of the native peoples that they had colonized. This was done ostensibly to “benevolently assimilate” and civilize their colonial subjects. A closer look at the educational programs of the colonial regimes will reveal that there were other motives which ranged from the practical (creation of a colonial work force) to the spiritual-cultural (transformation of cultural norms to conform with those of the colonizer). In the process, there were also some inadvertent results such as the introduction of ideas of nationalism and democracy into traditional societies. This study forms part of a larger study that will compare the educational programs of the British in Malaya/Burma, the French in Vietnam/Tonkin and the United States in the Philippines. By interrogating official documents and papers, the study will explore how these educational systems and programs were conceptualized and carried out. It will look at their goals or motives, as well as measures of success. As such, it will provide a glimpse at the process of social and cultural change as imposed from above. Studying these colonial regimes and their impact on education will help us not only to understand the colonial project but also to look at questions of identity, culture and society in post-colonial Southeast Asia.